Workforce skills across the urban-rural hierarchy - Jaison R. Abel; Todd M. Gabe; Kevin Stolarick (Federal Reserve Bank of New York, 2012)
This paper examines differences in the skill content of work throughout the United States, ranging from densely populated city centers to isolated and sparsely populated rural areas. To do so, we classify detailed geographic areas into categories along the entire urban-rural hierarchy. An occupation-based cluster analysis is then used to measure the types of skills available in the regional workforce, which allows for a broader measure of human capital than is captured by conventional measures. We find that the occupation clusters most prevalent in urban areas - scientists, engineers, and executives - are characterized by high levels of social and resource-management skills, as well as the ability to generate ideas and solve complex problems. By contrast, the occupation clusters that are most prevalent in rural areas - machinists, makers, and laborers - are among the lowest in terms of required skills. These differences in the skill content of work shed light on the pattern of earnings observed across the urban-rural hierarchy.
Keywords: R11; R12; O18; J24; 330; human capital; skills; occupations; urban-rural; earnings